"I Saw a Kingfisher": Grace and Ruin in Golding's The Spire - Yeager, Diane M. (Horizons, 1993)
William Golding, in The Spire, invites us to ask how we may know the will of God, and suggests that what we take to be the will of God is often simply the projection onto history of the disguised image of our private and self-absorbed desires. Though contemporary critics tend to interpret the novel as a sympathetic exploration of moral ambiguity rather than as a compelling condemnation of Jocelin's mortifying and death-dealing sin, the novel turns on the contrast between the drive toward dominion and the capacity for assent. The final salvific discovery, given form in Jocelin's mind by the experience of the apple tree and the kingfisher, is the overthrow of the will, its panicked drowning, in terrified apprehension of implacable glory and squandered gifts.